The drums of war are the drums of hunger: A comparative analysis of the use of food as a weapon in Darfur and Somalia - Kamphuis, Anneke Imke (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Political Science))--University of Stellenbosch, 2010.